Differences in Attitudes Toward Reading: A Survey of Pupils in Grades 5 to 8 - Nootens, Pascale; Morin, Marie-France; Alamargot, Denis; Gonçalves, Carolina; Venet, Michèle; Labrecque, Anne-Marie (Frontiers in Psychology, 2019)
Recent research on literacy has highlighted the impact of affective factors on learning to read. Among these factors, attitudes toward reading have been clearly shown to influence the development of reading skills and academic success. Nevertheless, differences in children’s attitudes across schooling have yet to be properly documented, especially for the French language and the transition between elementary and secondary education. In this cross-sectional study, our goal was to gauge the attitudes of French-speaking pupils across this transitional period. We therefore administered a computer-based questionnaire to 469 pupils in Grades Five to Eight in Quebec (Canada), to gather their views about leisure reading and academic reading. Results showed that their stated attitudes toward reading remained stable across the final two years of elementary school, as well as across the first two years of middle school, but differences were observed for the transition from one education level to the next, with stated attitudes toward reading being less positive in the latter.This effect, which was observed for both leisure and academic reading, concerned girls and boys alike. We discuss possible explanations for these differences in reading attitudes at this juncture in children’s schooling.